EVALUATION OF ADVENCE GREEN BUILDING BASED ON GBCI CERTIFICATION, CASE STUDY : LA CUCINA, SE - Mustafidul umam; Sugini Sugini (Ide dan Dialog Desain Indonesia (Idealog), 2021)
Green building is a concept as a response to global urban heat island problems, water pollution and ozone depletion. The concept of green building has been applied in various tools, none other than GBCI with six categories. This paper evaluates the La Cucina building in Seoul with the aim of knowing the extent to which GBCI is implemented outside the region as it should be and knowing the constraints and advantages of the rating tool. The method used is to make a La Cucina building simulation with Archicad software then evaluate the calculations with exel, velux and look for the building material literature and match it in the greenship tool. The results obtained in the existing building OTTV values and natural lighting have not reached the GBCI target, while for environmentally friendly materials and fabricated materials, they have not yet been fully achieved. Therefore, it was retested in accordance with the initial recommendations and results. The final results of OTTV, natural lighting, environmentally friendly materials and fabrication materials as expected and successful. The conclusion and recommendation of this paper is that OTTV can be achieved by measuring shading and replacing glass materials which have low Sc Glass and Uv values. While in lighting, 30% of the space on each floor has natural lighting. For environmentally friendly materials and fabricated materials, it has been achieved, evidenced by the material and fabrication certification from the factory. Keywords : Green Building, GBCI, OTTV, environmentally friendly materials, fabrication materials